2013
DOI: 10.1111/maec.12083
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tidal regime, diurnal phase, habitat and season on feeding of an intertidal crab

Abstract: The relationship between diet and feeding activity of intertidal crabs, and environmental cycles (tidal, daily and seasonal), habitat and level of the intertidal zone (high/low) was studied using Neohelice granulata (Brachyura, Varunidae) as a model. This is a semi‐terrestrial burrowing crab occupying different habitats in the Southwestern Atlantic coasts and estuaries from bare low intertidal mudflats to high intertidal salt marshes, and from fine, organic matter rich sediment to very coarse sediment with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 31 publications
2
24
0
1
Order By: Relevance
“…The results in Figure 4 show that partially purified amylase from the hepatopancreas of N. granulata also exhibited ability to hydrolyze glycogen, similarly to partially purified amylase from the copepod H. viduus (Dutta et al, 2006). The ability to hydrolyze starch and glycogen suggests the capacity of N. granulata to utilize glycogenic carbohydrates from vegetal and/or animal sources, which is in agreement with its dietary habits in the mudflat of the Mar Chiquita lagoon (Iribarne et al, 1997;Pinoni et al, 2011;Bas et al, 2014). The ability to hydrolyze glycogen could also be linked to the capacity for using this reserve in the hepatopancreas, which is a site of glycogen storage and exhibits a high content of free glucose (Pinoni et al, 2011).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The results in Figure 4 show that partially purified amylase from the hepatopancreas of N. granulata also exhibited ability to hydrolyze glycogen, similarly to partially purified amylase from the copepod H. viduus (Dutta et al, 2006). The ability to hydrolyze starch and glycogen suggests the capacity of N. granulata to utilize glycogenic carbohydrates from vegetal and/or animal sources, which is in agreement with its dietary habits in the mudflat of the Mar Chiquita lagoon (Iribarne et al, 1997;Pinoni et al, 2011;Bas et al, 2014). The ability to hydrolyze glycogen could also be linked to the capacity for using this reserve in the hepatopancreas, which is a site of glycogen storage and exhibits a high content of free glucose (Pinoni et al, 2011).…”
Section: Discussionsupporting
confidence: 67%
“…In most marine and brackish waters, the main dissolved inorganic ions come from NaCl; thus, salinity constitutes a measure of the water content of this dissolved salt (Romano and Zeng, 2012;Kültz, 2015). In the mudflats of the Mar Chiquita coastal lagoon, adult males of N. granulata prefer to feed during submersion periods but can also can eat sediments during emersion periods while the soil remains wet (Bas et al, 2014). Furthermore, they can tolerate high concentrations of zinc, copper, and manganese, which accumulate in the hepatopancreas (Beltrame et al, 2010(Beltrame et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…700 km in straight line from the studied sites. These data were reported by Bas et al (2005Bas et al ( , 2007Bas et al ( , 2008Bas et al ( , 2014 (1994,1996,2012).…”
supporting
confidence: 49%
“…The effect of other environmental factors, including salinity, quality or quantity of benthic food sources and productivity, had been suggested as possible causes of the differences between MC and SAO (Bas et al 2007). The effect of salinity cannot explain the observed differences between SAO and RSJ, since both sites have a high and constant salinity, and the notorious variation in the quality of food available for females seems to be a more plausible interpretation: it has been shown that the main food source for females is the organic matter of sediment (Bas et al 2014). If so, and since RSJ and MC had similar food quality, an interesting question remains open: why are fecundity and reproductive output higher in the former?…”
mentioning
confidence: 91%
“…Crabs could find denser patches of food accessible on sediment surface in the field, improving the food accumulation in stomachs. Furthermore, in natural conditions, diets are complemented with fresh plant leaves (those individuals that inhabit the mudflat and feed mainly on sediment consume plants to some extent and vice versa, Bas et al 2013), and with the occasional consumption of carrion, predation on larger preys such as polychaetes, and cannibalism, (D'Incao et al 1990, Lancia 2013.…”
Section: Discussionmentioning
confidence: 99%